The Effect of Tax System and Discrimination on Tax Evasion - Dimuk, Musdalifah; Ahmad, Hafsah (International Journal of Engineering and Technology, 2018)
This paper presents a study to investigate the effect of tax system and discrimination on tax evasion in Riau Province. The population of this investigation consists of all taxpayers registered in the Primary Tax Office inÂ Riau Province. The sampling was done using purposive sampling technique and proportional sampling. Total sample in this research is 222 respondents. The study designs a questionnaire in Likert scale to study the effects of two independent variables (tax system and discrimination) on tax evasion. Using regression technique, the study has determined positive and meaningful relationships between discrimination and tax evasion while tax system have no effect on tax evasion.Â Â